Metabolite profiling of some organs and the potential of Mukia javanica as an antihypertension - Pratami, Mentari Putri; Sujarwo, Wawan; Fendiyanto, Miftahul Huda; Yuniati, Ratna; Kurniyanto, Ifan Rizky; Widiayani, Nuniek; Seleiman, Mahmoud F.; Ali, Nawab; Anshori, Muhammad Fuad (Frontiers in Sustainable Food Systems, 2025)
Mukia javanica is a close relative of the cucumber (Cucumis sativus) used to treat hypertension in the Leuwiliang community. Cucumis sativus contains calcium, magnesium, potassium, and phosphorus, which help lower blood pressure. In contrast, the content of metabolite compounds that are useful for lowering blood pressure in M. javanica has not been previously reported. Therefore, this research aimed to identify and determine the secondary metabolite content contained in several M. javanica organs and determine potential compounds that function in treating hypertension. The method used is the gas chromatography-mass spectrometry (GCMS) method. The samples analyzed included several organs of M. javanica, such as roots, stems, leaves, and fruit. Several organs are tested to determine the part of the plant with the most potential secondary metabolite compound content. Data analysis used the R version 3.5.2 program and the Metaboanalyst program. Based on the test results, 98 secondary metabolite compounds were identified and divided into several compound classes, and the most significant number of compounds identified was the terpenoid compound group. The 13-Tetradecen-1-acetate (root), Oleic acid (fruit), Phytol (stem), and 4-hydroxy-3-nitrocoumarin (root) content in Mukia javanica has the potential to be antihypertensive. Based on correlation analysis, the metabolites Hexadecanoic Acid Methyl Ester, Squalene, Vitamin E, and Stigmasta-7,16-Dien-3 show high correlation values. The compound Hexadecanoic Acid Methyl Ester is found in all parts, and it is reported to be associated with antihypertension and antioxidants. In the future, this compound has the potential to be used as a raw material for antihypertensive drugs